Employment Vulnerability of People With Severe Mental Illness - Diby, Akissi; Lengagne, Pascale; Regaert, Camille (IDEAS Working Paper Series from RePEc, 2021)
Using French longitudinal register data, we compare the evolution of employment rates of persons with severe chronic mental illness, before and after the first medico-administrative recognition of the illness by the Statutory Health Insurance (SHI), with that of people without recognised mental illness. The study focuses on persons of working age having a work history before recognition. Our empirical approach relies on a double difference method with coarsened exact matching. Before illness recognition subjects had lower employment rates than those without mental illness but relatively high, reflecting their initial employment attachment. Results indicate that employment rates decrease sharply after recognition. A large employment rate gap between persons with and without severe mental illness develops during the four years following recognition. We examine whether the magnitude of the decrease is sensitive to the macroeconomic context. Findings show that the decline in employment rates was significantly more pronounced during the Great Recession compared with the pre-crisis period, amongst women. As a conclusion, this study points out that implementing coordinated early health and labour policies in the phase of the entry into the chronic-illness insurance scheme of the SHI might play a key role in preventing the detrimental effects of illness on economic and social conditions of persons with severe mental illnesses.